THE USE OF PLAY AS A FACILITATING TOOL TO PROMOTE THE DEVELOPMENT OF SOCIOEMOTIONAL SKILLS AT SCHOOL - Zanotto Bonamigo, Greice; Ricardo, Julia (Revista Gênero e Interdisciplinaridade, 2024)
This article aims to highlight the contributions of play to the development of Socio-Emotional Skills at school, given the relevance of this topic. To this end, a bibliographical review will be conducted that emphasizes the theoretical approaches of renowned researchers in the field of education, such as Jean Piaget, Lev Semenovich Vygotsky and Kishimoto, exploring their analyzes of the impact of play on child development. Furthermore, research will be analyzed that highlights the importance of Socio-Emotional Skills at school, establishing a relationship with the role of play in this process. Finally, some initiatives carried out in the Brazilian context will be presented, highlighting the positive results obtained.